Disease-Associated Mutations in the HSPD1 Gene Encoding the Large Subunit of the Mitochondrial HSP60/HSP10 Chaperonin Complex - Bross, Peter; Fernandez-Guerra, Paula (Frontiers in Molecular Biosciences, 2016)
Heat shock protein 60 (HSP60) forms together with heat shock protein 10 (HSP10) double-barrel chaperonin complexes that are essential for folding to the native state of proteins in the mitochondrial matrix space. Two extremely rare monogenic disorders have been described that are caused by missense mutations in the HSPD1 gene that encodes the HSP60 subunit of the HSP60/HSP10 chaperonin complex. Investigations of the molecular mechanisms underlying these disorders have revealed that different degrees of reduced HSP60 function produce distinct neurological phenotypes. While mutations with deleterious or strong dominant negative effects are not compatible with life, HSPD1 gene variations found in the human population impair HSP60 function and depending on the mechanism and degree of HSP60 dys- and malfunction cause different phenotypes. We here summarize the knowledge on the effects of disturbances of the function of the HSP60/HSP10 chaperonin complex by disease-associated mutations.